2014
DOI: 10.3892/mmr.2014.2736
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-mediated activation of the Src-epidermal growth factor receptor-Akt signaling cascade prevents bortezomib-induced apoptosis in hepatocellular carcinoma cells

Abstract: Proteasomes are essential for numerous cellular processes, including the cell cycle, regulation of gene expression and responses to cellular stress. Proteasome inhibitors are promising anticancer agents. The proteasome inhibitor bortezomib effectively suppresses certain types of cancer, including multiple myeloma and mantle cell lymphoma. However, bortezomib poorly inhibits solid tumors, including hepatocellular carcinoma. The activation of Akt represents an adaptive response that prevents bortezomib-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…It has been proposed that ROS might modify tyrosine residues, further altering phosphorylation of many protein kinases involved in cell signaling (Akhand et al, ). In support of this notion, recent study reported that ROS mediates the activation of the Src‐EGFR pathway (Hou et al, ). In the present study, levels of ROS in BALF were increased after O 3 exposure.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It has been proposed that ROS might modify tyrosine residues, further altering phosphorylation of many protein kinases involved in cell signaling (Akhand et al, ). In support of this notion, recent study reported that ROS mediates the activation of the Src‐EGFR pathway (Hou et al, ). In the present study, levels of ROS in BALF were increased after O 3 exposure.…”
Section: Discussionmentioning
confidence: 76%
“…In this case, O 3 exposure initially activated Src kinase, which in turn causes EGFR(Y845) phosphorylation leading to the subsequent autophosphorylation of EGFR(Y1068) (Wu et al, ). Another potential mechanism is suggested by O 3 ‐induced production of ROS (Hou et al, ). It has been proposed that ROS might modify tyrosine residues, further altering phosphorylation of many protein kinases involved in cell signaling (Akhand et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…5a). IR exposure induces ROS generation and ROS activates Src/AKT [37,38]. To determine if IR-induced ROS was involved in Src/AKT phosphorylation and senescence induction in the absence of integrin β4, we treated cells with NAC, a ROS scavenger, prior to irradiation of RKO cells ( Supplementary Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ROS/RNS can attack key biological molecules (including EGFR, NLR inflammasome) and modulate many signaling pathways (such as NF‐κB signaling) (Dostert et al, ; Wu et al, ; Hou et al, ). EGFR, a pivotal growth factor receptor possessing intrinsic tyrosine kinase activity, is a transmembrane protein and can be directly activated or transactivated in response to various of stimuli (Gschwind et al, ).…”
Section: Discussionmentioning
confidence: 99%